Olfactory processing in bipolar disorder, major depression, and anxiety. (13th February 2018) - Kamath, Vidyulata; Paksarian, Diana; Cui, Lihong; Moberg, Paul J; Turetsky, Bruce I; Merikangas, Kathleen R
Abstract : Objectives: Although olfactory abnormalities are well established in schizophrenia, considerably less work has examined olfactory performance in other neuropsychiatric conditions. In the current study, we examined odor identification, odor discrimination, detection threshold, and odor hedonic processing performance in individuals with bipolar I disorder (n = 43; n = 13 with psychotic features), bipolar II disorder (n = 48), major depressive disorder (MDD) (n = 134), anxiety (n = 48), and no mental disorder (n = 72) who participated in a community‐based family study. Methods: Best estimate DSM‐IV diagnoses were based on in‐depth personal interviews as well as interviews with family members. Olfactory tests were administered during an in‐person clinical visit and were compared using robust linear regression adjusting for age, sex, and psychiatric medication use, as well as nicotine use when necessary. Results: Compared to controls, odor identification performance was lower among individuals with MDD ( b = −1.37, 95% confidence interval [CI]: −2.50, −0.24) and bipolar I disorder ( b = −1.79, 95% CI: −3.51, −0.67). Among the latter group, performance was only reduced among those with psychotic features ( b = −3.49, 95% CI: −6.33, −0.65), particularly for pleasant odors ( b = −1.46, 95% CI: −2.51, −0.42). Those with MDD showed lower identification accuracy for neutral odors ( b = −0.63, 95% CI: −1.20, −0.06). Performances on measures of odor discrimination and detection threshold did not differ by diagnostic group. Conclusions: Collectively, these findings indicate that odor identification difficulties may exist in mood disorders, especially when psychotic features are present. In contrast, the global olfactory dysfunction observed in schizophrenia may not be a feature of other neuropsychiatric conditions.